2020
DOI: 10.4103/jcecho.jcecho_50_19
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical left ventricular dysfunction in severe obesity and reverse cardiac remodeling after bariatric surgery

Abstract: Aim: Obesity is associated with an increased cardiovascular risk. This study aimed to assess the role of echocardiography in the early detection of subclinical cardiac abnormalities in a cohort of obese patients with a preserved ejection fraction (EF) undergoing bariatric surgery. Methods and Results: Forty consecutive severely obese patients (body mass index≥35 kg/m2) referring to our center for bariatric surgery were enrolled in this prospective cohort study. Despite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 24 publications
(25 reference statements)
1
6
0
Order By: Relevance
“…There was no difference in ejection fraction between the groups, however GLS was lower in postbariatric women, suggesting better systolic function. Diastolic indices were also more favorable in the postbariatric group, with higher E/A ratio and TDI-E lat and E med, and lower E/E ratio and left atrial volume, which is consistent with findings in non-pregnant individuals following bariatric surgery 7,30,37,38 .…”
Section: Patel Et Alsupporting
confidence: 85%
“…There was no difference in ejection fraction between the groups, however GLS was lower in postbariatric women, suggesting better systolic function. Diastolic indices were also more favorable in the postbariatric group, with higher E/A ratio and TDI-E lat and E med, and lower E/E ratio and left atrial volume, which is consistent with findings in non-pregnant individuals following bariatric surgery 7,30,37,38 .…”
Section: Patel Et Alsupporting
confidence: 85%
“…There were no significant differences in age, sex, and BMI between the normal and impaired GLS groups. Previous studies have reported that GLS is impaired in aged, female, or overweight patients [ 5 , 6 ]. Furthermore, GLS reportedly declines with age without a significant decrease in LVEF [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the general population without cardiovascular disease or traditional risk factors, the absolute GLS difference between men and women is >1%, and women have better (lower) GLS [ 5 ]. Obese candidates for bariatric surgery have a high prevalence of preclinical systolic dysfunction and LVH or concentric remodeling, which is detectable in the early stage with echocardiography [ 6 ]. The lack of correlation between these factors and impaired GLS in our cohort may be due to the small sample size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study done by Frea et al, in 2020 involving 40 patients who underwent bariatric surgery, there was an improvement in GLS 10 months after surgery. 24 In 2019, a meta-analysis of 7 randomized controlled trials examining the outcome of bariatric surgery versus medical treatment for type 2 diabetes mellitus showed that bariatric surgery is superior and has a more persistent effect on type 2 diabetes mellitus remission compared to medical management. 25 reported when necessary.…”
Section: Sample Sizementioning
confidence: 99%